Dukungan keluarga dan komunitas sesama penderita: studi pada pasien dengan hemodialisis di rumah sakit - Windri Lesmana Rubai; Retna Siwi Padmawati; Yanri Wijayanto Subronto (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Support from spouse and hospital-based self help group members for hemodialysis patients in public hospitalPurpose: This study aims to document examples of social support given by hemodialysis friends and self-help group to people undergoing hemodialysis in the hospital.Method: This is a qualitative research with phenomenology research design. Subject was selected using purposive sampling based on criteria inclusion and maximum variation. Data were collected by in-depth interview, consisted of 11 informants (6 male and 5 female) with length of hemodialysis experience between 6 months to 2 years. In addition, family were also invited for in-depth interview. The validity of data were assessed through triangulation and peer debriefing.Results: This study documented examples of friendliness among people who undergoing hemodialysis in the hospital. Occasionally they schedule community meetings or just a joint meal between patients and families after the hemodialysis therapy schedule takes place. At such meetings, they can exchange experiences and transfer the information from the old members to the new one. The group involved activities outside the hospital, the group involved new members to work together at local and national events in support of chronic kidney diseases patients.Conclusion: Our findings show that depressed patient who undergoing the hemodialysis gained new perception of their diseases and got a support to continue their treatment through self-help group. This research emphasize the role of hospitals as entry points for sufferers to find groups of fellow sufferers whose social support programs.